Surgery of the breast : principles and art - Spear, Scott L.; Willey, Shawna C. (Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"This heavily illustrated two-volume atlas is the most comprehensive "how-to" reference on surgery of the breast. The world's leading surgeons describe and demonstrate the most advanced and successful techniques for all types of general surgery, aesthetic, and reconstructive procedures--oncologic management of breast disease, breast reconstruction, reduction mammoplasty and mastopexy, and augmentation mammoplasty. The text is illustrated throughout with over 4,100 drawings and full-color preoperative, intraoperative, and postoperative photographs. Editorial comments at the end of each chapter provide an alternative perspective and address current controversies. This thoroughly updated Third Edition features a greatly expanded section on augmentation mammoplasty. Other new chapters cover deep inferior epigastric perforator flap breast reconstruction, skin preserving delayed breast reconstruction, and nipple-sparing mastectomy. Coverage also includes new information on managing oncoplastic surgery, surveillance following breast reconstruction, reconstruction following tumor recurrence, and the role of stem cells"--Provided by publisher.